3D thermohydraulic modelling of geologically complex Alpine systems: Insights for geothermal resources exploration from simulating the Upper Aarmassif, Switzerland - Stefan Scheidler; Pièrre G. Christe; Eric Zechner; Michel A. Walde; Oliver S. Schilling; Jannis Epting (Hydrogeology Journal, 2026)
Mountainous regions such as Switzerland, which are characterized by highly complex geological and hydrogeological conditions, hold significant geothermal potential linked to tectonic settings and deep hydrothermal flow systems. However, geothermal exploration in such regions is challenged by geological and hydrogeological complexity, data scarcity, high uncertainty, administrative hurdles, as well as environmental and economic risks associated with drilling. Robust quantitative tools that maximize the value of the limited information available on the subsurface are needed to assess geothermal potential, productivity, and sustainability. Here, a step-by-step framework for the assessment of regional hydrothermal flow systems is presented. The framework consists of 3D geological modeling, 3D thermohydraulic modelling (3D-TH-model), and a systematic sensitivity analysis for the identification of the optimal structural model complexity. The framework is demonstrated on the hydrothermal systems of the Upper Aarmassif in the Swiss Alps. Results showed that thermal upwelling in the system is driven by strong topographic gradients and upward flux along more permeable tectonic faults and thrusts. The upwelling results in significantly elevated groundwater temperatures near the surface in the Rhône Valley, with temperatures exceeding 70 °C at depths of 1000 m and reaching ~100 °C at depths of 2000 m. These model outputs were verified by the few available vertical borehole temperature profiles, horizontal tunnel temperature profiles, groundwater recharge rates and hydraulic head distribution, 14 C-based groundwater residence times, and geothermometrically identified hydrothermal-reservoir-temperature estimates. The framework provides the basis for risk-reduced geothermal exploration, thereby supporting sustainable geothermal development—a significant step towards a decarbonized energy future.

Salt dissolution potential estimated from two-dimensional vertical thermohaline flow and transport modeling along a Transylvanian salt diapir, Romania - Eric Zechner; Horst Dresmann; Marius Mocuţa; Alex Danchiv; Peter Huggenberger; Stefan Scheidler; Stefan Wiesmeier; Iulian Popa; Alexandru Zlibut (Hydrogeology Journal, 2019)

Effects of tectonic structures, salt solution mining, and density-driven groundwater hydraulics on evaporite dissolution (Switzerland) - Eric Zechner; Markus Konz; Anis Younes; Peter Huggenberger (Hydrogeology Journal, 2011)

The southeastern border of the Upper Rhine Graben: a 3D geological model and its importance for tectonics and groundwater flow - Ina Spottke; Eric Zechner; Peter Huggenberger (International Journal of Earth Sciences, 2005)